Training on the use of corn sheller machine in Kutai Lama Village, Kutai Kartanegara - Andansari, Dita; Sihombing, Ruspita (Community Empowerment, 2021)
The corn sheller machine used by the Kutai Lama Village farmer group produces corn cobs that are cut or crushed, so it cannot be used as a medium for making mushrooms and worms. To solve this problem, the team developed a corn sheller machine and trained farmer groups to use the product. In this activity, two corn shelling machines were handed over and given training on how to use a corn sheller machine which is equipped with a 'belt cover' as a safety and added with a 'guide tool' so that the corn kernels do not spill. In addition, the machine is proven to increase the productivity of corn shelling activities. When compared with the manual method, the productivity increases to 4800%.